How local resources shape innovation and path development in rural regions. Insights from rural Estonia - Merli Reidolf; Martin Graffenberger (Journal of Entrepreneurship, Management and Innovation)
This paper examines the role of local resources (physical, human, immaterial, social and community, and financial) in shaping firm innovation and path development in rural areas. Existing research in spatially informed innovation studies has largely overlooked the place-specific resources of rural regions as innovation facilitating qualities. This paper addresses the following research questions: (i) what is the role of local rural resources in a firm’s innovation activities, and (ii) how do these resources shape regional development paths? We propose a framework that takes a holistic view of rural resources and their role in shaping innovation and regional development paths. The empirical analyses suggest that rural resources offer valuable and diverse opportunities for firm innovation, providing that firms (pro-)actively mobilize and purposefully exploit these resources as part of their innovation endeavors. We find that rural resources have the potential to extend and upgrade regional development paths and operate as ingredients to enrich existing paths with additional functions and, thereby, to make them more future-oriented. However, merely relying on rural resources does not suffice to facilitate substantial changes in regional paths. Our analyses are based on semi-structured interviews with representatives of firms located in rural Estonia, active in different manufacturing and service industries. This paper contributes to the emerging, but still fragmented, literature on rural innovation and offers a contextually grounded micro-level framework on the role of local rural resources for firm innovation in rural areas. Furthermore, the study adds an empirical contribution from a rarely studied Central and Eastern European regional context.